The effect of CSR on brand attitudes, brand image, and trust: A case of restaurants in Iran - Omidvar, Mohammadsadegh; Deen, Anisah (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Corporate social responsibility (CSR) has increased has received ongoing attention due to its influence on customer behavior thus, a conceptual model is put forward to investigate the effects of CSR on brand attitude, brand trust, brand image and ultimately brand equity. Data were collected via online questionnaires to restaurant customers in Tehran and a total of 468 responses were achieved. Multivariate analysis including confirmatory factor analysis (CFA) and structural equation modeling (SEM) was used to test the conceptual model. Results reveal that CSR has a significant effect on brand attitude, brand image, brand trust and brand equity. These results have major managerial implications particularly for restaurants that are engaged in CSR activities as findings indicate that engaging in CSR activities can lead to added value to their services. This study demonstrates that there is a new bias emerging among Iranian consumers moving towards restaurants adhering to social and environmental issues.